(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article analyzes the possibilities of using Blockchain distributed registry technologies to predict the crisis states of countries based on methods of comparative analysis and extrapolation. The scientific novelty of the work, according to the author, lies in the combination of the practical role of Blockchain technology and the theoretical importance of developing economic-resistant models for predicting an economic crisis